Сравнительная микроморфология нервного аппарата мочевыводящих путей позвоночных животных - Иванов, Н.М. (Вестник зоологии, 1973)
By means of silver salt impregnation the fine morphology of the nerve apparatus of urinary tracts was studied in various representatives of vertebrates (amphibians, reptiles, birds and mammals). In nerve plexi the walls of the ureters, urinary bladder and urethra numerous neurons of different shape are found with pericellular apparatuses on them. Receptor apparatuses are represented by free and incapsulated nerve endings. The greatest concentration of nerve elements is observed in pyelic-ureteral segment and ureteral orifices near the neck bf the bladder and in places of anatomic narrowings of the urethra.